The design, synthesis and biological evaluation of novel multiple targeting anti-cancer agents - Moran, Brian William (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2015)
The purpose of the work undertaken within this project was to design and synthesis novel anti-cancer targeting compounds building upon previous work undertaken under the supervision of Dr. John J. Walsh in the School of Pharmacy and Pharmaceutical Sciences.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin